Endometriosis as an immune-mediated disease: pathogenetic mechanisms and therapeutic strategies - Shifon, Sofia; Tyrinova, Tamara; Veretelnikova, Tatyana; Pasman, Natalia; Chernykh, Elena (Frontiers in Immunology, 2025)
Endometriosis, which affects approximately 10% of women of reproductive age, is a complex inflammatory disease with significant immune system disturbances caused by an inadequate immune response to retrograde menstruation and leading to the establishment of immune evasion mechanisms by ectopic tissue. This review provides an analysis of the immunopathogenetic mechanisms of endometriosis based on 198 high-quality publications selected from 1,209 potentially relevant articles in the PubMed, Scopus, Web of Science, and Google Scholar databases for the period 1927–2025. The study revealed that endometriosis is associated with profound alterations in both innate and adaptive immunity. Key pathogenetic mechanisms include macrophage dysfunction with a shift to the M2 phenotype, reduced cytotoxic activity of NK cells, complement system activation with proinflammatory and proangiogenic effects, a predominant Th2 response with an increase in Treg cells, and B-lymphocyte activation with autoantibody production. The cytokine profile is characterized by a concurrent increase in both pro-inflammatory mediators (IL-1β, IL-6, TNF-α) and immunosuppressive factors (IL-10, TGF-β). The complement system contributes to pathogenesis through C3a/C5a-mediated inflammation, angiogenesis promotion, and interactions with dysbiotic endometrial microbiota. Different forms of endometriosis have specific immunological features: ovarian endometriosis combines local immunosuppression with systemic inflammation, adenomyosis is characterized by pro-inflammatory changes with a Treg cell deficiency, and deep infiltrating endometriosis is distinguished by the activation of the IDO1/COX-2/MMP-9 signaling pathway and complement-mediated tissue destruction. Understanding the specifics of immunopathogenesis opens new avenues for developing targeted immunotherapy, which may include modulating immune cell functions, using cytokine inhibitors, blocking immune checkpoints, and employing nanotechnological approaches.